Skeletal Health in Premenopausal Women with Type 1 Diabetes: A Scoping Review - Eugenia Vlachou; Anastasia Ntikoudi; Dimitra Anna Owens; Despoina Rizikou; Afroditi Tsalkitzi; Eleni Evangelou; Athanasios N. Tsartsalis (Diabetology, 2026)
Background: Type 1 diabetes (T1D) is increasingly recognized as a condition associated with impaired skeletal health and increased fracture risk. Although osteoporosis is usually considered more clinically relevant after menopause, diabetes-related skeletal alterations may begin earlier in life. This scoping review aimed to map the available evidence on bone-health outcomes in premenopausal women with T1D. Methods: A scoping review was conducted following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews (PRISMA-ScR). PubMed/MEDLINE, Scopus, Web of Science, CINAHL and the Cochrane Library were searched, supplemented by Google Scholar and manual screening of reference lists. Eligible studies examined bone mineral density (BMD), fracture history or fracture risk, bone turnover markers, quantitative ultrasound parameters, bone microarchitecture, or other skeletal outcomes in premenopausal women or women with T1D. Results: Seven studies met the eligibility criteria. The included studies were mainly observational and varied in sample size, age range, diabetes duration, skeletal sites assessed, and bone-assessment methods. Most studies reported lower BMD or less favorable skeletal parameters in premenopausal women with T1D compared with women without diabetes, particularly at peripheral or hip-related skeletal sites. Quantitative ultrasound studies suggested impaired peripheral skeletal properties, while one MRI-based study identified trabecular microarchitectural deficits. Several studies also reported altered bone turnover markers and associations between poorer glycemic control, adverse health behaviors or diabetes-related complications, and poorer bone outcomes. Fracture data were limited and were based on previous or self-reported fractures. Potential determinants of skeletal health were variably reported across studies, with more consistent consideration of body mass index and selected lifestyle or reproductive factors than of autoimmune, nutritional, medication-related, and detailed reproductive variables. Conclusions: Available evidence indicates that premenopausal women with T1D may exhibit early alterations in skeletal health, including differences in BMD, peripheral bone measures, bone turnover, and microarchitecture. These findings highlight the potential importance of considering bone health before the menopausal transition. However, prospective data on fragility fractures remain limited, and further longitudinal studies incorporating detailed reproductive, metabolic, and clinical factors are needed to clarify the long-term skeletal implications and inform future risk-assessment strategies.